Non-chemotoxic induction of cancer cell death using magnetic nanowires - Contreras, Maria F (Int J Nanomedicine, 2015)
In this paper, we show that magnetic nanowires with weak magnetic fields and low frequencies can induce cell death via a mechanism that does not involve heat production. We incubated colon cancer cells with two concentrations (2.4 and 12 μg/mL) of nickel nanowires that were 35 nm in diameter and exposed the cells and nanowires to an alternating magnetic field (0.5 mT and 1 Hz or 1 kHz) for 10 or 30 minutes. This low-power field exerted a force on the magnetic nanowires, causing a mechanical disturbance to the cells. Transmission electron microscopy images showed that the nanostructures were internalized into the cells within 1 hour of incubation. Cell viability studies showed that the magnetic field and the nanowires separately had minor deleterious effects on the cells; however, when combined, the magnetic field and nanowires caused the cell viability values to drop by up to 39%, depending on the strength of the magnetic field and the concentration of the nanowires. Cell membrane leakage experiments indicated membrane leakage of 20%, suggesting that cell death mechanisms induced by the nanowires and magnetic field involve some cell membrane rupture. Results suggest that magnetic nanowires can kill cancer cells. The proposed process requires simple and low-cost equipment with exposure to only very weak magnetic fields for short time periods.